Managing the ageing experience : learning from older people - Tanner, Denise, 1960- (Ageing and the lifecourse., 2010)
Current social policy recognises that older people should be treated as experts in their own lives and be actively involved in their care. This book explores what can be learned from older people's experiences of managing ageing. Direct connections are made between the everyday experiences and perspectives of older people, related research and theoretical perspectives. This yields an engaging and informative analysis of how older people manage the ageing experience and what this means for policy and practice directed at promoting older people's wellbeing.